Analisis Perbandingan Kinerja Keuangan Rasio Car, Nim Dan Roa Bank Syariah Dan Bank Konvensional Yang Terdaftar Di Bursa Efek Indonesia - Mariyam, Siti; Iqbal, Johandri; Ayuningrum, Niken (Journal of Applied Accounting And Business, 2024)
This research is motivated by the phenomenon of the increasingly rapid growth of banking in Indonesia, in particular, both sharia and conventional banking. Where in general there are differences in the legal umbrella used and in the form of profit recovery. One of the factors that banks must pay attention to in order to continue to survive is the performance (financial condition) of the bank. The aim of this research is to analyze the significant differences between the financial performance of Islamic banking and conventional banking based on CAR, NIM and ROA ratios. The population in this research is sharia banks and conventional banks listed on the Indonesia Stock Exchange (BEI) for the 2022-2023 period. The sampling technique uses a purposive sampling method. The type of data analysis used in research is using quantitative data analysis techniques which only use number calculations and then draw conclusions. The testing technique used in this research uses descriptive statistical tests and independent sample tests. This research uses SPSS Version 23 statistical software. The results of this research are that there is no difference in the financial performance of Islamic banking and conventional banking based on CAR, NIM and ROA ratios